INFLUENCE OF SOWING PERIOD ON THE FORAGE PRODUCTIVITY SMOOTH BROME GRASS - Марініч, Любов; Мелешко, Ірина (SWorldJournal, 2024)
Topicality. Increasing the production of cheap and high-quality fodder is an urgent problem for animal husbandry. But it is possible to solve this issue based on the intensification of fodder production. To create a strong fodder base, it is necessary to